Evaluation and Validation of the Modified Reflux Symptom Questionnaire–Electronic Diary in Patients With Persistent Gastroesophageal Reflux Disease. Issue 1 (January 2020) - Andrae, David A.; Hanlon, Jennifer; Cala, Mary Lynn; Scippa, Kayla; Graham, Christina; Witherspoon, Brooke; Shao, James Z.; Reasner, David
Abstract : OBJECTIVES: This study aimed to examine the validity of the modified Reflux Symptom Questionnaire–electronic Diary (mRESQ-eD) through patient input and psychometric testing of the questionnaire to support use in clinical trials in patients with persistent gastroesophageal reflux disease (GERD) and in accordance with Food and Drug Administration guidance on patient-reported outcome instruments. METHODS: Cognitive interviews were conducted with patients (n = 30) to evaluate the interpretability and content validity of draft mRESQ-eD items. Patient data from a phase 2b clinical study (ClinicalTrials.gov identifier: NCT02637557) on persistent GERD served to aid in the construction of weekly scores for heartburn severity, regurgitation severity, and total GERD severity. These scores' psychometric properties were also evaluated. RESULTS: Minor modifications were made to the draft mRESQ-eD based on patient feedback to improve interpretability and clarity of the instrument. Psychometric analysis suggested that an 8-item version of the mRESQ-eD was best suited to the clinical data. The internal consistency was found to be high (Coefficient ω = 0.95). Retest reliability and convergent validity were strong for a heartburn weekly severity score, regurgitation weekly severity score, and total GERD severity score. DISCUSSION: The final 8-item mRESQ-eD is a reliable and valid instrument with good psychometric properties for use in clinical trials in patients with persistent GERD. The mRESQ-eD may be considered for inclusion in clinical trials for persistent GERD and potentially positioned, in consultation with Food and Drug Administration, as endpoints to characterize treatment benefit.